2020
DOI: 10.1038/s41598-020-74597-6
|View full text |Cite
|
Sign up to set email alerts
|

Optical observation of needles in upward lightning flashes

Abstract: Why lightning sometimes has multiple discharges to ground is an unanswered question. Recently, the observation of small plasma structures on positive leaders re-ignited the search. These small plasma structures were observed as pulsing radio sources along the positive leader length and were named “needles”. Needles may be the missing link in explaining why lightning flickers with multiple discharges, but this requires further confirmation. In this work we present the first optical observations of these intrigu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
80
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(101 citation statements)
references
References 15 publications
13
80
3
Order By: Relevance
“…If the needles twinkle at a regular rate, and the distance between needles is about equal to the speed of the leader times half the time between twinkles (which is the case in their data), then the twinkles from nearby needles will naturally appear to occur out-of-phase even if the needles have no interaction at all. Close examination of Figure 3 in Saba et al (2020) shows support not only for downward-going waves, but also equal evidence for upward-going waves, which strongly implies that downward-going twinkle-inducing waves are an observational artifact.…”
Section: Needle Structure Along the Positive Leadermentioning
confidence: 83%
See 2 more Smart Citations
“…If the needles twinkle at a regular rate, and the distance between needles is about equal to the speed of the leader times half the time between twinkles (which is the case in their data), then the twinkles from nearby needles will naturally appear to occur out-of-phase even if the needles have no interaction at all. Close examination of Figure 3 in Saba et al (2020) shows support not only for downward-going waves, but also equal evidence for upward-going waves, which strongly implies that downward-going twinkle-inducing waves are an observational artifact.…”
Section: Needle Structure Along the Positive Leadermentioning
confidence: 83%
“…et al (2020) were somewhat shorter than those observed in Hare et al (2019) and Pu and Cummer (2019). Saba et al (2020) was even able to show that propagation of one 73-m long needle was away from the positive leader with a speed of about 2.7 × 10 5 m/s, and that a negative leader developed from the location of a needle, consistent with Hare et al (2019) and Pu and Cummer (2019), and Saba et al (2020) was able to confirm a hypothesis proposed by Hare et al (2019), that the first needle twinkle occurs about 100 m or so behind the tip of the positive leader. Finally, Saba et al (2020) was also able to show that needles are the result of a corona-brush split, which is where the corona in front of a positive leader splits into two different sections in a failed attempt to branch.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…The new positive leader propagation mechanism that is here suggested does not only have just implications for long air discharges in the laboratory. As the streamers optically observed at the heads of natural positive leaders 11 – 13 show some similarities with those in the laboratory discharge, the proposed mechanism also introduces a new physical process which needs to be assessed when studying leader-related lightning phenomena such as intermittent propagation of positive leader 39 44 , recoil leaders 45 47 and needles 12 , 48 , 49 . According to this new mechanism, the leader will propagate stepwise using short steps, as previously suggested by Bazelyan 17 .…”
Section: Discussionmentioning
confidence: 94%
“…More recently, Saba et al. (2020) reported clear corona brush (corona streamer formation) surrounding and diverging outward from the positive leader head, as captured by Phantom cameras at distances of 0.3 and 1.9 km. Because the observations of CSZ with fine time resolution are still lacking, the physical characteristics of CSZ is not very clear yet.…”
Section: Discussionmentioning
confidence: 99%